Research Methods for Science - Marder, Michael P. (Cambridge : Cambridge University Press, 2011)
A unique introduction to the design, analysis, and presentation of scientific projects, this is an essential textbook for undergraduate majors in science and mathematics. The textbook gives an overview of the main methods used in scientific research, including hypothesis testing, the measurement of functional relationships, and observational research. It describes important features of experimental design, such as the control of errors, instrument calibration, data analysis, laboratory safety, and the treatment of human subjects. Important concepts in statistics are discussed, focusing on standard error, the meaning of p values, and use of elementary statistical tests. The textbook introduces some of the main ideas in mathematical modeling, including order-of-magnitude analysis, function fitting, Fourier transforms, recursion relations, and difference approximations to differential equations. It also provides guidelines on accessing scientific literature, and preparing scientific papers and presentations. An extensive instructor's manual containing sample lessons and student papers is available at www.cambridge.org/Marder.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Science projects